The Taliban’s Curricular Attack on Higher Education in Afghanistan: A New Reality for Higher Education in Afghanistan - Mohibbi, Abdul; Coburn, Noah (International Higher Education, 2023)
In two short years, universities in Afghanistan have seen a drastic drop in enrollment due to the Taliban ban on women in higher education and a culture of surveillance and fear. At the same time, however, the Taliban have moved to begin to restructure curricula and universities themselves to impose their own versions of conservative religiosity, in stark contrast with the expansion of universities under the previous government.